2015
DOI: 10.1038/srep08362
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of injury-induced anterior subcapsular cataract in the mouse: a model of lens epithelial cells proliferation and epithelial-mesenchymal transition

Abstract: The mouse lens capsular injury model has been widely used in investigating the mechanisms of anterior subcapsular cataract (ASC) and posterior capsule opacification (PCO), and evaluating the efficacy of antifibrotic compounds. Nevertheless, there is no available protocol to quantitatively assess the treatment outcomes. Our aim is to describe a new method that can successfully quantify the wound and epithelial-mesenchymal transition (EMT) markers expression in vivo. In this model, lens anterior capsule was punc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 27 publications
(38 reference statements)
1
36
0
1
Order By: Relevance
“…37 Briefly, the injured mice were killed and their eyes were enucleated. And then the lens were isolated under a dissecting microscope and fixed in 100% methanol for 1 h at RT.…”
Section: Methodsmentioning
confidence: 99%
“…37 Briefly, the injured mice were killed and their eyes were enucleated. And then the lens were isolated under a dissecting microscope and fixed in 100% methanol for 1 h at RT.…”
Section: Methodsmentioning
confidence: 99%
“…LncRNA XLOC_009704/n344497, also known as lncRNA RMST, was down-regulated in nuclear ARC compared to transparent lens capsules. RMST is an emerging regulatory lncRNA in epithelial-to-mesenchymal transition (EMT) and cell differentiation [45,46], which may be related to the pathogenesis of cataract [47,48]. Previous studies identified a microRNA, miR-135a, whose expression was correlated to the lncRNA RMST.…”
Section: Discussionmentioning
confidence: 99%
“…All animal experiments were approved by the Animal Ethics Committee of Kunming Medical University. The mouse model of injury‐induced ASC was established as described previously . Before the surgical procedure, the mice (body weight [BW] = 30‐50 g, n = 6, male) were given a single intraperitoneal injection of pentobarbital sodium (70 mg/kg).…”
Section: Methodsmentioning
confidence: 99%